STRUCTURE OPTIMIZATION DESIGN FOR THE ROTARY WORKTABLE OF GANTRY MACHINING CENTER BASED ON RESPONSE SURFACE METHODOLOGY - ZHENG Bin; ZHANG JingDong (Jixie qiangdu)
Taking the rotary worktable of a gantry machining center as the research object,the static and dynamic characteristics analysis and optimization design are carried out by using the finite element method. In order to increase the stiffness and reduce the weight of rotary worktable,the main design parameters are tested by Box-Behnken experiment design.Based on the design of experiment,sensitivity analysis is carried out for design parameters and the response surface model is established. Then,the multi-objective optimization algorithm is adopted to optimize the response surface model and combined with the production technique to determine the best optimization scheme. The results of optimization show that the maximum deformation is reduced by 36. 8%,the first natural frequency is increased by 5. 4% and the weight is decreased by 2. 6% by using above method to optimize the rotary worktable,which providing a new idea for the design and optimization of the rotary worktable.